2021
DOI: 10.3390/brainsci11081047
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Spinal Manipulation on Oculomotor Control in Children with Attention Deficit Hyperactivity Disorder: A Pilot and Feasibility Study

Abstract: Attention Deficit Hyperactivity Disorder (ADHD) is a prevalent, chronic neurodevelopmental disorder that affects oculomotor (eye movement) control. Dysfunctional oculomotor control may result in reading or educational difficulties. This randomized controlled crossover study sought to investigate the feasibility of a larger scale trial and effects of a single session of spinal manipulation on oculomotor control in children with ADHD. Thirty children participated in the study and were randomized into either cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Studies have identified a role of frontal eye fields in the regulation of attention ( Funahashi and Andreau, 2013 ). One recent study found that chiropractic adjustment led to improved oculomotor control and reading time in children with ADHD ( Cade et al, 2021 ). The study’s authors proposed that as oculomotor control is thought to rely on accurate sensory processing, the changes in the afferent input after spinal adjustment could have accounted for the observed positive treatment response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have identified a role of frontal eye fields in the regulation of attention ( Funahashi and Andreau, 2013 ). One recent study found that chiropractic adjustment led to improved oculomotor control and reading time in children with ADHD ( Cade et al, 2021 ). The study’s authors proposed that as oculomotor control is thought to rely on accurate sensory processing, the changes in the afferent input after spinal adjustment could have accounted for the observed positive treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Since these reviews were published, one case series ( n = 4), and multiple case reports described improvements in ADHD potentially related to chiropractic adjustments ( Wittman et al, 2009 ; Alcantara and Davis, 2010 ; Muir, 2012 ; Fairest et al, 2019 ). A pilot and feasibility randomized controlled crossover trial ( n = 30) found that a single session of chiropractic adjustment led to a significant improvement in reading time measured by an eye tracker in children with ADHD ( Cade et al, 2021 ). While reading time can provide insights into certain aspects of attention and eye movements related to reading, it may not capture the full range of ADHD symptoms or assess other domains of impairment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spinal manipulation also improves proprioception, as observed through a post-manipulative reduction in Joint Position Error (JPE) values [ 77 , 78 , 79 ]. It has been suggested that the post-manipulative effect on saccadic movements is most likely due to improved proprioceptive input from the cervical spine [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is often accompanied by an audible “cracking” noise resulting from cavitation of the joint. Spinal manipulation is also most commonly known for its ability to reduce musculoskeletal pain [ 29 ], and it has also been shown to improve proprioceptive input and the function of those brain networks involved in producing various eye movements [ 30 , 31 , 32 ]. However, despite the known effects of altering proprioceptive input into the brain, the effects of cervical spinal manipulation on saccadic eye movements and in patients diagnosed with (PCS), to the best of our knowledge, have not been directly investigated.…”
Section: Introductionmentioning
confidence: 99%